Bifidobacterium: a probiotic for the prevention and treatment of depression - Li, Jiayu; Wang, Junyu; Wang, Meiyu; Zheng, Li; Cen, Qiuyu; Wang, Fangfang; Zhu, Li; Pang, Rizhao; Zhang, Anren (Frontiers in Microbiology, 2023)
Depression is a common psychological disease, which has become one of the main factors affecting human health. It has a serious impact on individuals, families, and society. With the prevalence of COVID-19, the incidence of depression has further increased worldwide. It has been confirmed that probiotics play a role in preventing and treating depression. Especially, Bifidobacterium is the most widely used probiotic and has positive effects on the treatment of depression. The mechanisms underlying its antidepressant effects might include anti-inflammation and regulation of tryptophan metabolism, 5-hydroxytryptamine synthesis, and the hypothalamus-pituitary-adrenal axis. In this mini-review, the relationship between Bifidobacterium and depression was summarized. It is hoped that Bifidobacterium-related preparations would play a positive role in the prevention and treatment of depression in the future.